2016
DOI: 10.1177/0892705715618745
|View full text |Cite
|
Sign up to set email alerts
|

The effect of beverage storage packets (Tetra Pak™) waste on mechanical properties of wood–plastic composites

Abstract: The present study seeks to investigate the effect of beverage storage carton (Tetra Pak™) waste and maleic anhydride-grafted polyethylene (MAPE), coordinated to light polyethylene on the mechanical properties of wood–plastic composites. Four levels of Tetra Pak™ (0%, 10%, 20%, and 30%) and two levels MAPE (0% and 3%) were used. At first, the materials were mixed in a Haake internal mixer and then the samples were made through the injection molding method. The results showed that the composites containing 30% o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 6 publications
0
9
0
Order By: Relevance
“…He et al studied the mechanical performance of WPCs prepared by blending tea residue with high-density polyethylene (HDPE) [11]. Ebadi et al investigated the physical and mechanical properties of WPCs based on wood powder to beverage storage carton waste in varying proportions [12]. Kajaks et al have studied the influence of modifiers on the rheological property and thermal stability property of plywood production residues polypropylene composites [13].…”
Section: Introductionmentioning
confidence: 99%
“…He et al studied the mechanical performance of WPCs prepared by blending tea residue with high-density polyethylene (HDPE) [11]. Ebadi et al investigated the physical and mechanical properties of WPCs based on wood powder to beverage storage carton waste in varying proportions [12]. Kajaks et al have studied the influence of modifiers on the rheological property and thermal stability property of plywood production residues polypropylene composites [13].…”
Section: Introductionmentioning
confidence: 99%
“…Ebadi et al [34] blended LDPE (60%) and poplar timber powder (0 to 40%) with shredded aseptic cartons (0 to 30%); in some trials 3% MAPE (malic anhydride-grafted polyethylene) replaced 3% LDPE. Analysis of the injection molded samples showed that the composites containing 30% cartons and 3% MAPE had the highest strength and tensile modulus as well as the highest impact resistance.…”
Section: Blendsmentioning
confidence: 99%
“…In part of the research, the cardboard is processed and incorporated into new composites [ 45 , 46 ]. Several investigations were carried out to evaluate the mechanical properties of cardboard made from recycled beverage cartons [ 47 , 48 , 49 , 50 , 51 ]. Other researchers used the waste cardboard in the form in which it was obtained [ 52 ].…”
Section: Introductionmentioning
confidence: 99%